(untitled) (Nonconventional Technologies Review, 2022)
December is always a good time to look back on the accomplishments of the year that closes and make plans for the one that is ready to begin. In 2022, our community, like everybody else, made important efforts to overcome the challenges of returning to normal after two years of interruption. Many research endeavors needed completion, many students returned to the course halls and the laboratories, and many ideas for a better future required work. We believe that all our members have risen to these challenges, and we even had the opportunity to celebrate 25 years since the launch of our journal with a heartfelt moment in Sovata, in December 2-4, 2022.